GAMBARAN PEMBELAJARAN SALAFIAH DI PONDOK PESANTREN BUSTANUL HUDA DESA PAGAR PUDING KECAMATAN TEBO ULU KABUPATEN TEBO PROVINSI JAMBI - -, DAHLIA - (Pendidikan Sosiologi, 2014)
General description of learning salafiah in boarding school, especially boarding school Bustanul Huda Fences Pudding has not been known picture of the process of learning. This is related to the position of boarding schools as institutions pendididkan this modernization era still maintain old traditions. On the other hand boarding schools should adopt development of modern science. The purpose of this research are: Overview of Learning Salafiah At boarding school Bustanul Huda Fences Pudding, the reason the boarding school are still using conventional methods in boarding school Bustanul Huda Fences pudding. This study used a qualitative retrofitting, while this type of research is deskripstif. Data used primary data and secondary data. Data collection techniques are observation, interviews, and documentation. The results found that the learning process is done salafiah Bustanul Huda Islamic boarding school in the village of Fence pudding a.) Description of learning salafiah b) The material studied is the recitation of Quran and yellow books, c.) Salafiah lessons held every day except Friday, dilasanakan at 14:30 pm until 21:00 pm. The reason for the teachers who teach in boarding school Bustanul Huda Pagar pudding still using conventional methods because a) they are considered more appropriate to use the conventional method for learning salafiah, and b) also follows the earlier scholars.